Development and Validation of a Four-Tier Diagnostic Instrument for Chemical Kinetics (FTDICK) - Habiddin Habiddin; Elizabeth Mary Page (Universitas Gadjah Mada, 2019)
The present study outlines the development and validation of a four-tier diagnostic instrument to explore first year undergraduate students’ understanding of chemical kinetics (FTDICK). The four-tier instrument is a recent format and has been applied only sparsely in a limited number of subject areas, not including chemical kinetics. This study confirms the importance of a four-tier approach in fully investigating students’ poor knowledge and understanding. The FTDICK described here involves 20 questions with a confidence level linked to both the question tier and the reason tier. The development of the instrument followed the procedure used for the two-tier instrument developed by Treagust and involves (1) testing & interviewing, (2) identifying & collecting students’ unscientific ideas, (3) developing the prototype FTDICK, (4) validating the prototype FTDICK, and (5) developing the final FTDICK. The initial steps revealed a number of areas of misconceptions to be explored in the final instrument. The instrument has been developed and the prototype tested using international cohorts of students from the University of Reading, UK and two Indonesian Universities. Comprehensive item analysis on the results showed the instrument to be valid and reliable and suitable for identifying students’ understanding of chemical kinetics. This study confirms the importance of a four-tier approach for investigating students’ prior knowledge and understanding.